The Modified Iliopubic Tract Repair—A Pain-Free Alternative - Ali, Iqbal; Dikshit, Vashisht; Manerikar, Kshitij; Dholakia, Mirat; Save, Maitreyee (The Surgery Journal, 2018)
Background The open preperitoneal repair offers the benefits of placing the mesh in the preferred position while avoiding the disadvantages of laparoscopic repair.Methods A total of 60 patients with bilateral inguinal hernias were randomized to undergo either the standard Lichtenstein meshplasty or the modified iliopubic tract repair in a teaching hospital. Outcomes measured were immediate postoperative pain, return to activity, and delayed neurological complications.Results Patients who underwent the iliopubic tract repair walked out of bed faster than the Lichtenstein group (6.3 hours vs 7.4 hours, p < 0.0001) and experienced significant lower pain as charted by visual analogue scale scores (3.28 vs 2.71 on day 1, 2.16 vs 1.71 on day 2, 1.92 vs 1.08 on day 3; p < 0.05). Delayed complications like chronic inguinal pain and numbness were not seen in the iliopubic tract group. However, this difference was not statistically significant (p > 0.05).Conclusion The iliopubic tract repair offers an excellent alternative to the Lichtenstein meshplasty, and is associated with lower postoperative pain, earlier return to work, and lower delayed neurological complications.
Keywords: hernia; inguinal; herniorrhaphy; mesh; chronic pain; pain; postoperative